Wing planform analysis with taper ratio and expansion segment variation with lifting line theory - Dafa, Amien S.; Nugroho, Gunawan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Amien S. Dafa* & Gunawan NugrohoDepartment of Engineering Physics, Institut Teknologi Sepuluh Nopember Kampus ITS Sukolilo, Surabaya Indonesia 60111*Corresponding author: asd12amien@gmail.com; gunawan@ep.its.ac.idReceived 6 October 2022, Received in revised form 5 April 2023Accepted 5 May 2023, Available 30 November 2023ABSTRACTTapered wing shape of a planform wing is still widely used amongst airplane and UAVs with subsonic speed. In the design process, a good consideration for a good taper ratio of a wing is required to obtain the optimal and distribution for the desired function of an aircraft. Additionally, addition of expansion segment on wing planform shape is often used to increase the performance of wings without the increase of wingspan. Several methods to analyze a wing shape are experimentation, computational luid dynamics, and analytical calculation. Analyzing with analytical calculation will present limited, but accurate outcomes due to the assumptions that are made during the calculation. This method, however, is inexpensive. This is why analytical calculation is still a common method to use in the design process of an aircraft, particularly in the early phase. Five variants of taper ratio and 3 variants that with expansion segment is analyzed using the Lifting Line Theory that utilizes Fourier series at subsonic speed. The results are the values of and with respect to and the distribution of and along the wingspan. Increasing the taper ratio results in the decrease of and the increase of , while adding an expansion segment will give results that are dependent on the added segment’s taper ratio.